Regional Variables in Color Preferences for Space Design and an Evaluation on Their Priorities (Journal of Interior Design and Academy, 2023)
Colors are one of the most important elements that guide us and affect our perceptions in every aspect of our lives. However, these effects vary from person to person and there are some parameters that cause this. The more accurately these parameters are taken into account, the more successful the effect desired to be created with colors on users will be. When it comes to space design, one of the crucial role affects to perception of color belongs to regional variables. While regional variables differ, the affect of a color on the user is changing a lot. In this study, the criteria under the heading of regional variables of the color selection criteria classification model created as a result of examining the studies on color selection criteria in the literature were examined. After this review, a group of interior architecture students and architects were given informational training on the effects of regional variables criteria on color selection and were asked to evaluate the priorities of the criteria among themselves. As a result of their evaluations, the priority rankings of regional variables are presented in this study to guide designers.
Keywords: Color preference; region and color perception; religion and color perception; culture and color perception; language and color perception